Arabidopsis Seedling Lethal 1 Interacting With Plastid-Encoded RNA Polymerase Complex Proteins Is Essential for Chloroplast Development - Jiang, Deyuan; Tang, Renjie; Shi, Yafei; Ke, Xiangsheng; Wang, Yetao; Che, Yufen; Luan, Sheng; Hou, Xin (Frontiers in Plant Science, 2020)
Mitochondrial transcription termination factors (mTERFs) are highly conserved proteins in Metazoans. Plants have many more mTERF proteins than animals. The functions and the underlying mechanisms of plant mTERFs remain largely unknown. In plants, mTERF family proteins are present in both mitochondria and plastids and are involved in gene expression in these organelles through different mechanisms. In this study, we screened Arabidopsis mutants with pigment-defective phenotypes and isolated a T-DNA insertion mutant exhibiting seedling-lethal and albino phenotypes (sl1). The SL1 gene encodes an mTERF protein localized in the chloroplast stroma. The sl1 mutant showed severe defects in chloroplast development, photosystem assembly, and the accumulation of photosynthetic proteins. Furthermore, the transcript levels of some plastid-encoded proteins were significantly reduced in the mutant, suggesting that SL1/mTERF3 may function in chloroplast gene expression. Indeed, SL1/mTERF3 interacted with PAP12/PTAC7, PAP5/PTAC12, and PAP7/PTAC14 in the subgroup of DNA/RNA metabolism in the plastid-encoded RNA polymerase (PEP) complex. Taken together, the characterization of the plant chloroplast mTERF protein SL1/mTERF3 that associated with PEP complex proteins provided new insights into RNA transcription in the chloroplast.